AB1051 Dish prevalence in patients affected by severe cardiovascular diseases. (23rd January 2014) - Zincarelli, C.; Iervolino, S.; Vitale, D.F.; Di Gioia, L.; Miniero, E.; Rengo, C.; Pappone, N.
Abstract : Background: DISH is characterized by ossification of entheses and ligaments, especially the anterior spinal longitudinal ligament. It is almost asymptomatic, although polyarticular pain, morning stiffness, and limited spinal motion have been described. The etiology is unknown and its prevalence varies according to the population evaluated. Several factors may be associated with DISH, in particular: obesity, high waist circumference ratio (WC), hypertension, diabetes, hyperinsulinemia, dyslipidemia. Recently, it has been reported that DISH patients are frequently affected by metabolic syndrome (MetS) and exhibit an increased risk for cardiovascular morbidity. Objectives: Evaluate the prevalence of DISH and its relationship with vascular risk factors (VRFs) in patients with severe cardio-vascular diseases (CVDs). Methods: 521 consecutive patients admitted to a cardiac intensive rehabilitation program were enrolled. Only subjects undergone coronary artery bypass grafting (CABG), heart valve replacement (HVR) or affected by congestive heart failure (CHF) entered the study. Patients underwent to rheumatologic examination, blood sample collections including fasting glucose, triglycerides, total and HDL-cholesterol, ESR, CRP, and chest radiographs. Waist circumference, body mass index (BMI) and blood pressure were recorded. Information about gender, age, smoking habit and previous CVDs were collected. MetS was diagnosed according to NCEP criteria. DISH was established when the radiological criteria of Resnick and Niwayama were fulfilled. Results: 422 subjects were eligible for this study. The total prevalence of DISH in the setting was 30.2%. In details, 29, 9%, 22% and 40.2% in CABG, CVR and CHF groups respectively. Patients with DISH showed a significantly higher BMI, WC and older age. No significant differences were observed according to other VRFs. Conclusions: This is the first study aimed to assess the prevalence of DISH in patients affected by severe CVDs. Only older age, higher BMI and WC were significantly associated with DISH. Of interest, increasing evidences demonstrate that adipose tissue is metabolically active representing a source of inflammatory mediators, known as adipokines. Moreover, obesity may be associated with the insulin-resistance syndrome. As previously suggested, insulin, promoting the differentiation of mesenchymal cells into chondrocytes with enchondral ossification, might contribute to the ossification of entheses. However, the role played by insulin and other growth factors in the pathogenesis of DISH needs further investigations. In conclusion, even if DISH may exhibit low clinical expression, subjects affected by severe atherosclerotic CVDs reporting limited spinal motion and back pain should be investigated for DISH. References: Mader R et al. Extraspinal manifestations of diffuse idiopathic skeletal hyperostosis. Rheumatology 2009;48:1478–1481 Mader R et al. Metabolic Syndrome and Cardiovascular Risk in Patients with Diffuse Idiopathic Skeletal Hyperostosis. Semin Arthritis Rheum 2009;38:361-365 Kiss C et al. Risk factors for diffuse idiopathic skeletal hyperostosis: a case control study. Rheumatology (Oxford) 2002;41:27-30. Akune T et al. Insulin secretory response is positively associated with the extent of ossification of the posterior longitudinal ligament of the spine. J Bone Joint Surg 2001;3A:1537-44 Disclosure of Interest: None Declared